Thyme Plant Powder (Thymus vulgaris) Improves the Production Performance of Laying Hens by Affecting Ovarian Follicles - M. Ebrahimi; H. Ghaderi Chaparabad; I. S. M. Al-Moussawi; M. H. Hosseini; S. A. Mirghelenj (Tropical Animal Science Journal)
The present experiment investigated the effects of different levels of thyme powder on performance, blood biochemical parameters, reproductive system morphometry, and egg quality traits at different storage temperatures in old laying hens. For this purpose, in a completely randomized design, 144 laying hens (Hy-line-W36) aged 65 weeks were assigned to 3 treatments, 6 replications, and 8 birds each. Experimental diets were corn-soy based, including 0%, 0.25%, and 0.5% thyme powder (TP). At the end of the experimental period (8th week of the experiment), 6 eggs were selected from each replicate and kept at temperatures of 4 and 25 °C for 30 days to determine the internal quality. The results showed that the egg weight of birds fed with diets containing 0.25% and 0.5% TP was significantly higher than control ones (p<0.05), but egg mass and feed conversion ratio were higher in the 0.5% group. Triglycerides and cholesterol decreased in the egg yolk and blood serum of birds fed 0.5% TP comparing control birds (p<0.05). At a temperature of 25 °C, the use of 0.5% TP compared to the control treatment increased the Haugh unit but decreased the albumin pH compared to the control treatment and 0.25% TP (p<0.05). Laying hens fed a diet containing 0.5% TP had larger white follicle numbers than birds fed a control diet and 0.25% TP groups (p<0.05). In conclusion, 0.5% TP supplement in the diet of laying hens can increase performance and the number of large white follicles and decrease the level of triglycerides and cholesterol in egg yolk and blood serum.